2010
DOI: 10.1016/j.brainres.2010.08.051
|View full text |Cite
|
Sign up to set email alerts
|

Postural control and attentional demand during adolescence

Abstract: In the present study we aimed to determine the attentional cost of postural control during adolescence by studying the influence of a cognitive task on concurrent postural control. 38 teenagers aged 12 to 17 years and 13 young adults (mean age = 26.1) stood barefoot on a force platform in a semi-tandem position. A dual-task paradigm consisted of performing a Stroop or a COUNTING BACKWARD task while simultaneously standing quietly on a firm or foam support surface. Different centre of pressure (CoP) measures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 46 publications
5
55
0
2
Order By: Relevance
“…Previous studies have extensively evaluated various kinds of secondary tasks such as cognitive load [26][27][28][29][30][31][32], physical load [33][34][35], visual load [32,33,[36][37][38], and auditory load [36,39,40].…”
Section: Previous Studies On Postural Stabilitymentioning
confidence: 99%
“…Previous studies have extensively evaluated various kinds of secondary tasks such as cognitive load [26][27][28][29][30][31][32], physical load [33][34][35], visual load [32,33,[36][37][38], and auditory load [36,39,40].…”
Section: Previous Studies On Postural Stabilitymentioning
confidence: 99%
“…Therefore, when the level of difficulty of the postural task increases, Attentional Demands and Postural Task Difficulty the attentional resources allocated to postural control would also increase. A number of studies reported that in a dual task condition, postural steadiness can decrease concurrently or not with the performance of a secondary task in adolescents (Palluel et al, 2010), in young adults (Andersson et al, 1998;Pellecchia, 2003) and in elderly individuals (Shumway-Cook & Woollacott, 2000). The cross-domain competition model (Lacour et al, 2008) can account for this dual task interference.…”
Section: Influence Of the Dual Task Condition On Postural Parametersmentioning
confidence: 99%
“…It could be argued that compared with more complex cognitive tasks used in the literature, such as counting backwards (Brown, Shumway-Cook, & Woollacott, 1999;Palluel et al, 2010), performing Stroop tasks (Dault, Geurts, et al, 2001;Palluel et al, 2010) or arithmetic tasks (Vuillerme & Vincent, 2006;Weeks, Forget, Mouchnino, Gravel, & Bourbonnais, 2003), the use of a simple RT task as a secondary task did not require a high level of attention. Nevertheless, the performance of a simple RT task has the advantage of being measurable with a single variable compared with usually two parameters (i.e., the percentage of correct answers and the total number of answers) for more complex cognitive tasks.…”
Section: Influence Of the Dual Task Condition On Rtmentioning
confidence: 99%
See 1 more Smart Citation
“…Postural control has been considered to be an automatic system [13], but recent studies suggested that attentional processes are involved in the regulation of posture during simple or more complex tasks, especially when the latter involves attentional processes [14, 15]. …”
Section: Introductionmentioning
confidence: 99%